Microbiological profile of milk of Curraleiro Pé-Duro and Pantaneiro cattle breeds (Research, Society and Development, 2020)
The microbiological quality of raw milk can be directly influenced by the health of the animals, hygiene procedures performed during milking and storage conditions of the product. Given the need to characterize the microbiological aspects related to milk production of the bovine herds of the breeds Curraleiro Pé-Duro and Pantaneiro, 333 samples of raw milk were evaluated from the count of aerobic microorganisms mesophilic, psychrotrophic, Staphylococus coagulase positive as well as the determination of the most likely number of coliforms at 30°C and 45°C. Results showed low levels of contamination of milk samples by mesophils (7.5x101 - 8.7x103 CFU/ml - Hard Foot Currall/1.8x102 - 8.6x102 CFU/ml- Pantaneiro), psychrotrophic (2 - 1.4x102 CFU/ml / 2, 6x101 - 1.4x102 CFU/ml), Coagulase positive Staphylococcus (4 - 5.2x102 CFU/ml/ 1.1x102 - 7.6 x102 CFU/ml), coliforms at 30°C( 2.0 - 40.2 NMP/ml / 0.6 - 21.9 NMP/ml) and coliforms at 45°C (0.9-14.8 NMP/ml / 0.4- 20.3 NMP/ml). These results demonstrate the potential that the cattle herds of the breeds Curraleiro Pé-Duro and Pantaneiro present regarding the microbiological quality of the milk, the adequacy of the product to the sanitary legislation as well as the technological viability of this food matrix in the production of dairy products.